Enzymatic Study of Gills of Fish as Good Biomarkers of Environmental State of Fluoride Pressure - Aziz1, Farha; Azmat2, Rafia (Asian Journal of Chemistry, 2011)
The effect of fluoride on the activity level of alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase in gills at two sublethel concentration of fluoride was assessed. Fluoride has long been recognized to influence the activity of various enzymes and send false messages, which are amplified by processes of signal transduction. Results showed that enzymes activities were significantly altered due to which protein carbohydrate metabolism was disturb. Changes in three biomarkers of key enzymes of protein carbohydrate were related to metabolism of fish at both concentrations of fluoride. The carbohydrate concentration initially decreases which later on increases at both concentration with the time. Non-significant depletion of total protein in gills tissue was observed (p < 05). It was concluded that fluoride do produce toxic effect on physiology of fish gill, which may be associated with increased ionic permeability.